Pengaruh Pelatihan, Kompetensi Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Kereta Api Indonesia KAI (Persero) Daop 9 Jember Stasiun Probolinggo - Putri, Ika Murnia; Haris, R Abdul; Tumini, Tumini (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to determine the partial, simultaneous and dominant influence of training, competency and organizational culture on employee performance at PT. ΚΑΙ (Persero) Daop 9 Jember Probolinggo Station. The population of this research is employees of PT. ΚΑΙ (Persero) Daop 9 Jember Probolinggo Station. The data collection technique uses a questionnaire. Apart from that, this research used a sample of 39 respondents with a sampling method, namely saturated sampling. This type of research is causal associative. Data processing in this research uses SPSS version 22. Data analysis methods include validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, hypothesis testing and dominance testing. The results of this research show that training (X1) has a positive and significant effect on employee performance (Y) with a t-test value of 3,325 and is at a significance of 0,002, competency (X2) has a significant positive effect on employee performance (Y) with a t-test value of 3,485 and is at a significance of 0,001 and organizational culture (X3) has a significant positive effect on employee performance (Y) with a t test value of 2,442 and is at a significance of 0,020. The results of statistical analysis obtained an Fcount value of 17,462 > 2,87 and a significance value of 0,000 < 0,05. So there is a joint influence of the training variables (X1), competency (X2) and organizational culture (X3) on employee performance at PT. KAI (Persero) Daop 9 Jember Probolinggo Station. And the competency variable has a dominant influence with a standardized beta coefficient value of 0.434.